Perancangan Sign System Sebagai Sarana Informasi Klinik Flora di Bandar Lampung - Harry Abryan, Oky; Moussadecq, Ade (IMAGIONARY, 2024)
Flora Clinic has a vision, which is to become the first clinic of choice to provide the best service for the audience. The unstructured sign system as a visual representation of location markers at the Flora clinic is difficult to realize the best service that is prioritized by the manager. The sign system is a medium for human interaction with public spaces through visual forms. The existence of a sign system in a public space can help the public know the location of the place that will be the destination. The design of the sign system as a means of information for the Flora clinic in the city of Bandar Lampung uses a qualitative approach research method. namely the research method used to observe the condition of natural objects, where a researcher is the main key instrument of research. The design of Flora's clinical sign system uses a creative method, namely mind mapping. Tony Buzan said that mind mapping is a method by grouping ideas in a structured framework to transfer the thoughts in the brain into written or image form.